Interior of the Bethania Mill. - (:unkn) unknown (Forsyth County Public Library, 2009)
Photo made in the 1970s.
Interior of the Bethania Mill. Products manufactured at the mill were sold under the name of Bernard Milling Company.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth